Business management of KSU XXX at Sukatani Village in iroet tea agroindustry - Dinda Vergy Vidya (Research Institute for Tea and Cinchona, 2017)
Every business people must have a good management and appropriate in managing the business. The process of business activity requires every bussiness people to think systematically in establishing a good and appropriate business management. If it is not done, it will threaten business continuity. Business management KSU XXX is currently facing a problem that threatens the business continuity of the cooperative. There is no bailout, weak competitiveness and many partner farmers out of the cooperative membership. Considering this, a research has done to analyze business management strategy KSU XXX in maintaining agroindustry Teh Iroet. The research was conducted at one of the production centers of smallholder tea farmers in Garut. TheÂ KSU XXX, Sukatani Village, Cilawu Sub-district, which is the first cooperative formed by the smallholder tea farmers and obtaining UTZ and Lestari Certificates. This research is a qualitative research conducted in the form of case study. The result of the research shows that KSU XXX business management strategy to maintain Iroet Tea agroindustry is to run a saving program for partner farmers in lieu of cooperative saving and loan program that has been abolished. Conducting information and financial information disclosure system of cooperatives to its partners